Rapid surface functionalization of carbon fibres using microwave irradiation in an ionic liquid. Issue 39 (31st March 2016) - Beggs, Kathleen M.; Perus, Magenta D.; Servinis, Linden; O'Dell, Luke A.; Fox, Bronwyn L.; Gengenbach, Thomas R.; Henderson, Luke C.
Abstract : Carbon fibre surfaces have been successfully modified using molecular grafting under low power microwave irradiation (20 W) in both 1, 2-dichlorobenzene and emimTFSI. Results showed an improved IFSS by 18% for organic solvent and 28% for ionic liquid. Abstract : The modification of carbon fibre surfaces has been achieved using a novel combination of low power microwave irradiation (20 W) in both an ionic liquid (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) and an organic solvent (1, 2-dichlorobenzene). The use of the ionic liquid was superior to the organic solvent in this application, resulting in a higher density of surface grafted material. As a consequence, carbon fibres treated in the ionic liquid displayed improved interfacial adhesion in the composite material (+28% relative to untreated fibres) compared to those treated in organic solvent (+18%). The methodology presented herein can be easily scaled up to industrially relevant quantities and represent a drastic reduction in both reaction time (30 min from 24 h) and energy consumption, compared to previously reported procedures. This work opens the door to potential energy and time saving strategies which can be applied to carbon fibre manufacture for high performance carbon fibre reinforced composites.